FRI0261 B cell stimulating cytokines baff, IL-21 and IL-33 mrna expression are elevated coordinately in active rnp autoantibody+ sle. (23rd January 2014) - Greidinger, E. L.; Pignac-Kobinger, J.; Garza Romero, A. C.; Perumal, N. B.; Kondragunta, V.; Hoffman, R. W.
Abstract : Background: We examined a cohort of 79 consecutive patients classified as anti-ribonuclear protein (anti-RNP)+ systemic lupus erythematosus (SLE). All patients provided RNA samples obtained after providing informed consent. There were 73 female and 6 male subjects. Disease duration ranged from 0 to 453 months with a median of 37.5 months. SLE Disease Activity Index (SLEDAI) ranged from 0 to 31 with a median of 6. The goal of this study was to characterize gene expression profiles in active and inactive RNP autoantibody+ SLE versus healthy blood donors. Methods: Gene expression profiling was performed using Affymetrix microarrays on 79 patients and 30 healthy blood donors. mRNA from the 109 samples passed quality control and were analyzed using Affymetrix U133 Plus 2.0 expression arrays to determine gene expression, and data were compared after normalization using Robust Multichip Average algorithm. Statistical analyses were performed using two-sample t-test or univariate regression analysis. Results: BAFF, IL-21, IL-33, and CXCL13 mRNA expression was significantly higher in patients versus healthy controls (p<2E-8) while ICOS and CXCR5 were lower in patients (p<3.7E-18). There were strong correlations between expression of these genes, especially in patients with more active disease as defined by SLEDAI of 6 or greater. BAFF, IL-21, IL-33, and CXCL13 were high in patients with active disease. In addition, several of these were coordinately regulated. We found correlation for BAFF vs ICOS (p<0.02); BAFF vs CXCR5 (p<0.02); IL-21 vs ICOS (p<0.0001); IL-21 vs CXCR5 (p<0.0001) and IL-33 vs ICOS (p<0.02). Conclusions: There was elevation of mRNA expression for the B cell stimulatory cytokines BAFF, IL-21 and IL-33 in active RNP+ SLE supporting the concept that these are potentially important therapeutic targets for treatment of SLE in the presence of autoantibodies. In addition, the observed differences of mRNA expression of factors influencing B cell migration and trafficking, ICOS and CXCL13-CXCR5, and the apparent coordinate change of these with other B cell stimulator cytokines (BAFF, IL-21 and IL-33) in active SLE suggests that these may also be of importance in disease pathogenesis. Disclosure of Interest : E. Greidinger Consultant for: Eli Lilly & Company, J. Pignac-Kobinger: None Declared, A. Garza Romero: None Declared, N. Perumal Shareholder of: Eli Lilly & Company, Employee of: Eli Lilly & Company, V. Kondragunta Shareholder of: Eli Lilly & Company, Employee of: Eli Lilly & Company, R. Hoffman Shareholder of: Eli Lilly & Company, Employee of: Eli Lilly & Company